2023
DOI: 10.7759/cureus.33357
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Psychiatric Comorbidities and Quality of Life As Well As Brain‐Derived Neurotrophic Factor (BDNF) Concentrations Among Patients Suffering From Acne Vulgaris: A Systematic Review and Meta-Analysis

Abstract: Acne vulgaris usually affects the dermal layer of the skin and is revealed frequently in young adulthood and adolescence. It has serious psychosocial comorbidities. We conducted the present systematic review and meta-analysis to elucidate the association of acne vulgaris with psychiatric comorbidities and quality of life as well as the brain-derived neurotrophic factor (BDNF) level. A systematic review and meta-analysis of the published articles were carried out following the recommendations of the Preferred R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…The face is treated as a predisposing location for acne; however the back and upper part of the chest are also commonly involved [1,2]. Many studies demonstrated that acne predisposes to secondary psychiatric disturbances, like depression and anxiety [4,12]. Also, patients with acne are at increased risk for suicidal thoughts and attempts [13].…”
Section: Discussionmentioning
confidence: 99%
“…The face is treated as a predisposing location for acne; however the back and upper part of the chest are also commonly involved [1,2]. Many studies demonstrated that acne predisposes to secondary psychiatric disturbances, like depression and anxiety [4,12]. Also, patients with acne are at increased risk for suicidal thoughts and attempts [13].…”
Section: Discussionmentioning
confidence: 99%
“…In Almutawa et al 's systematic review and meta-analysis 2023, it has been shown that the psychological disturbances in infertile women are higher than in men, and this difference in couples needs further investigation [14]. Chachavomich et al 2010 showed that women's quality of life is more affected by infertility than men study, which was a systematic review [12], .…”
Section: Introductionmentioning
confidence: 99%
“…A cne vulgaris (AV) is a chronic inflammatory skin condition that affects a majority of adolescents and young adults 1,2 and is associated with many adverse physical and psychological effects on quality of life. 1,3 Oral isotretinoin (13-cis-retinoic acid) can induce complete or nearcomplete resolution of AV in most patients, with prolonged clearance after completion of therapy; it is considered to be the most effective treatment for severe nodular AV and is the only therapy shown to consistently provide long-term AV clearance after completion of a recommended course of therapy. 1,4 Due to its poor aqueous solubility, isotretinoin has historically required ingestion with food-specifically a high-fat meal with each dose-to ensure optimal absorption and consistent plasma concentrations of isotretinoin.…”
Section: Introductionmentioning
confidence: 99%